Technology Usage Standard Development Guidelines of School Administrators under The Secondary Educational Service Area Office Maha Sarakham - A-no, Kittiwat; Ruangsuwan, Chayakan (Interdisciplinary Academic and Research Journal, 2022)
Digital technology for education is an important tool in providing quality education that covers all ages, all target groups, which there are guidelines for developing digital technology systems for education, teaching and learning, and lifelong learning with a wide range of flexibility. Therefore, it is necessary for school administrators to have standards for the use of technology by school administrators. Thus, the research objectives were to 1) study the current state, the desired state, and the primary needs of technology usage standard development, and 2) study the technology usage standard development guidelines for school administrators in two phases. Phase 1: stratified random sampling method from the 372; the consensus index was 0.80–1.00, the current condition was 0.62-0.85, the desirable condition was 0.50-0.85, and the confidence level was 0.97. Phase 2: Interviewing 7 experts with the interview form. The statistics were Percentage, Mean, and Standard Deviation. The findings were as follows: 1) the current condition of the Technology Usage Standard Development Guidelines of School Administrators in general and each aspect was at the middle level in descending order, the desirable condition of the Technology Usage Standard Development Guidelines of School Administrators in general and each aspect was at the high level in descending order, the principal needs for the Technology Usage Standard Development Guidelines of School Administrators are in terms of the learning management, the Visionary Planner and Empowering and Leader Systems Designer and Connected Learner and Equity and Citizenship Advocate, respectively. 2) the Technology Usage Standard Development Guidelines of School Administrators is manual which contains principle reason and objective. The overall manual evaluation results were appropriateness and the feasibility was at the highest level.